Infrasound emitting at the start of a space rocket launch - Yehor Zahrevskyi; Halyna Sokol (Challenges and Issues of Modern Science)
The analysis of acoustic radiation during the launch of a heavy space rocket is the main goal of this work. Particular attention is paid to the determination of sound pressure levels in the vicinity of the rocket body and its potential effect on the body, flexible connections and internal devices. Additionally, the generation of infrasonic waves in the Earth's atmosphere and their interaction with atmospheric phenomena are investigated.